1985
DOI: 10.1111/j.1528-1157.1985.tb05662.x
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Vitamin B6 Metabolism in Brains of Genetically Epilepsy‐Prone Rats

Abstract: The status of vitamin B6 in brains of genetically epilepsy-prone and epilepsy-resistant rats was ascertained by measuring the concentrations of pyridoxal phosphate and the activities of pyridoxal kinase in the hippocampus, basal ganglia, cerebellum, and cerebral cortex, as well as in the entire brain. The concentrations of pyridoxal phosphate in whole brain of control rats and seizure-prone rats did not vary significantly from each other and were 1.2 +/- 0.02 and 1.2 +/- 0.03 microgram/g, respectively. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…By thoroughly investigating the molecules involved in functional remodeling of the spinal cord in remote cortexes, we discovered that PDXK is substantially upregulated in the motor cortex after SCT. It has been reported that the function of PDXK is prominently enhanced in the whole brain tissue of humans, embryos, and fetuses ( Bukin Iu and Ivanova, 1976 ; Shin et al, 2004 ), as well as in the whole brain of in epilepsy-prone and epilepsy-resistant rats ( Ebadi et al, 1985 ). Additionally, PDXK is expressed in the porcine brain cortex ( Gao et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…By thoroughly investigating the molecules involved in functional remodeling of the spinal cord in remote cortexes, we discovered that PDXK is substantially upregulated in the motor cortex after SCT. It has been reported that the function of PDXK is prominently enhanced in the whole brain tissue of humans, embryos, and fetuses ( Bukin Iu and Ivanova, 1976 ; Shin et al, 2004 ), as well as in the whole brain of in epilepsy-prone and epilepsy-resistant rats ( Ebadi et al, 1985 ). Additionally, PDXK is expressed in the porcine brain cortex ( Gao et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%